Prevalence of hypertension and its associated risk factors among police personnel of a metropolitan city - Kumar, Arunesh; Gautam, Praveen B; Prasad Pore (Asian Journal of Medical Sciences, 2023)
Background: Hypertension is one of the diseases of occupational origin. It is ranked 5th among the 10 most important categories of occupational illness. Police personnel constitute a special occupational group with exposure to violence at work, which directly and indirectly affects their health. Various studies have reported significantly high prevalence of stress-related disorders such as hypertension, diabetes, and coronary heart disease among the policemen and found police occupation as a prominent risk factor for coronary heart disease. Aims and Objectives: This study aims to estimate the prevalence of hypertension among police personnel of a metropolitan city. Materials and Methods: A cross-sectional study was conducted among the police personal of a metropolitan city for a period of 1 year. Three hundred and fifty police personnel were contacted and interviewed using pre-designed, pre-tested, semi-structured pro forma. Police personnel were screened by taking two B.P. readings. Data analysis was done using SPSS 20.0 Statistical software. Chi-square/Fisher’s exact test was used to find the association. Statistical significance was considered at P<0.05. Results: The prevalence of hypertension was 28% in the present study including 6% already detected and 22% newly detected. On multivariate logistic regression analysis, factors which were identified as risk factors for the development of hypertension among policemen were smoking, less physical activity, use of extra salt, mixed diet, and body mass index. Conclusion: The prevalence of hypertension was high among police personnel. Effective intervention strategies such as lifestyle modification along with health-care strategies must be planned to keep the police force healthy and vigilant.